Penjelajahan Orang Prancis dan Penelitian Sejarah Alam di Nusantara Pada Masa Kolonial - Gani Ahmad Jaelani (Jurnal Sejarah Citra Lekha, 2022)
This article seeks to elaborate the research on natural history carried out by French naturalists in Indonesia during colonial period. The tropical nature attracted many European naturalists to conduct research in order to gain economic advantages from the natural richness. The curiosity toward the alien nature always came with the observation to the people living in that region. Nevertheless, not all the research was carried out by the plan. In the case of French naturalists, the research that they performed in this region was conducted coincidently while they were visiting this region. This article analyzes how the French naturalists made their research on natural history in the Archipelago. It examines as well the objects that interested them. Lastly, it shows to what extent the colonial knowledge was formed through the encounter between the Europeans and the local people.